2014
DOI: 10.1590/s0100-204x2013000700007
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Resumo -O objetivo deste trabalho foi determinar a precisão experimental na avaliação da massa de matéria verde de nabo forrageiro, em cenários formados por combinações de tamanhos de parcela e número de tratamentos e de repetições. Utilizaram-se os dados de massa de matéria verde de 3.456 unidades experimentais básicas de 0,5×0,5 m (0,25 m 2 ). Os cenários (1.728) foram planejados e formados pela combinação de seis tamanhos de parcela (0,25, 0,50, 1,00, 1,50, 2,00 e 2,25 m 2 ), i tratamentos (i = 5, 6,..., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
7
1
8
Order By: Relevance
“…Traits such as thousand seed weight (3.57%), protein (1.63%), cycle (0.78%), height (0.70%), lodging degree (0.38%) and hectoliter grain weight (0.24%) showed little contribution concerning variability. These results were different from the outcomes reported by Amabile et al (2013b), who found a contribution of 11.15%, for cycle, and 1.53%, for class 1.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Traits such as thousand seed weight (3.57%), protein (1.63%), cycle (0.78%), height (0.70%), lodging degree (0.38%) and hectoliter grain weight (0.24%) showed little contribution concerning variability. These results were different from the outcomes reported by Amabile et al (2013b), who found a contribution of 11.15%, for cycle, and 1.53%, for class 1.…”
Section: Resultscontrasting
confidence: 99%
“…The two-rowed materials located on the left side of the plot showing greater distances, and the six-rowed barley genotypes located on the right side and which were more grouped. Amabile et al (2013b) found the same type of grouping.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Essa metodologia diferencia-se da utilizada por Cargnelutti Filho et al (2014a) por contemplar mais tamanhos de parcela e por incluir cenários com o delineamento de blocos ao acaso, comumente utilizados em experimentos em campo; conforme sugerido pelos autores.…”
Section: Methodsunclassified